Contribution to the knowledge of the genus Linum (Linaceae) in Veracruz, Mexico - Burgos-Hernández, Mireya; Castillo-Campos, Gonzalo (Instituto de Ecología, A.C., 2019)
Background and Aims: Linum is the largest genus in the Linaceae family and has a wide socio-economic importance. The taxonomy of the group is still unknown in Veracruz, despite being the third most floristically diverse state in Mexico. The aims of this work were to know the specific richness of the genus Linum and provide tools for its correct identification in the Veracruz state.Methods: Linum specimens collected in Veracruz and deposited in the herbaria CHAPA, ENCB, MEXU and XAL were reviewed, as well as the scanned specimens available on the TROPICOS and JSTOR Global Plants webpages. Simultaneously, a preliminary list of species was generated based on regional floristic studies. Determination and description of specimens were carried out using keys from different taxonomic treatments and floras, as well as the analysis of the information available in the literature and digital databases.Key results: Eight species of Linum distributed in Veracruz were identified, of which three constitute new verified records for the state and four are considered endemic to the country. A dichotomous key for identification, photographs, morphological descriptions, synonymy, and ecological data are provided. Distribution maps are included and the range of distribution is extended for some taxa.Conclusions: Fifty percent of the species identified for Veracruz are endemic to Mexico, of which Linum orizabae is the one with the greatest presence in the state. Three rare or infrequent species that had not been formally registered for Veracruz are included, all of them vulnerable to degradation and habitat loss. This, together with multiple detected identification errors, reflects the limited knowledge of the group and the need to inventory, analyze and characterize in an integral framework the Linaceae diversity in the region, and in general, in the country.